Effect of 5E Learning Cycle Model on Academic Performance of Senior Secondary School Students in Biology in Maiduguri Metropolis, Borno State, Nigeria - Abubakar Hamman-Tukur; Fati Shettima Abani; Ummi Asheik Gana (EDUMALSYS Journal of Research in Education Management, 2026)
Although improving biology achievement remains a major concern in secondary education, evidence on the effectiveness of the 5E Learning Cycle Model in the context of senior secondary schools in Maiduguri Metropolis remains limited. This study examined the effect of the 5E Learning Cycle Model on the academic performance of senior secondary school students in Biology and investigated whether the effect varied by gender. A quasi-experimental design was employed among 864 SSS1 Biology students, from which 86 students (38 males and 48 females) were selected. The sample size was determined using Cochran’s table, the school was selected through purposive sampling, and the students were randomly assigned to experimental and control groups, with 43 students in each group. Data were collected using the researcher-developed Biology Achievement Test, which yielded a Cronbach’s alpha reliability coefficient of 0.79, and were analyzed using Analysis of Covariance and effect size statistics. The findings revealed that the 5E Learning Cycle Model had a statistically significant positive effect on students’ academic performance, with post-test scores favoring those taught with the model (F = 55.018, p = .000, ηp² = 0.402). The results further showed that the effect of the model varied significantly by gender in favor of female students (F = 6.482, p = .013, ηp² = 0.073), indicating a medium effect size. These findings demonstrate that the 5E Learning Cycle Model is an effective instructional approach for improving students’ achievement in Biology and suggest its value for more inclusive and responsive classroom practice. The study therefore contributes empirical support for learner-centered science pedagogy and implies that the Borno State Ministry of Education should promote the adoption of the 5E Learning Cycle Model in the teaching of Biology in senior secondary schools.